Avantree / Muhammad Arif Kamsani … [et al.] - KAMSANI, MUHAMMAD ARIF; AG JALIL, AG BENNY; MOHD BORHAN, NUR ADRIANA (2020)
Avantree Company are known as avantronics designs, develops and manufactures innovative high quality of products. Avantree engineers are meticulous in their materials selection, and design to enhance or preserve the unmatchable value or costs ratio high-end products. Avantree's designs manufactures, and delivers useful and fun solutions for laptop user and multi-task people in the Americas, Europe, and Asia through major retailers and online. This company was incorporated in 1996 shortly after responding to a need in the marketplace.